Tidal marsh restoration : A synthesis of science and management - Burdick, David M.; Roman, Charles T. (The Science and Practice of Ecological Restoration, 2012)
Many coastal tidal marshes have been significantly degraded by roadways and other projects that restrict tidal flows, limiting their ability to provide vital ecosystem services including support of fish and wildlife populations, flood protection, water quality maintenance, and open space. Tidal Marsh Restoration provides the scientific foundation and practical guidance necessary for coastal zone stewards to initiate salt marsh tidal restoration programs. The book compiles, synthesizes, and interprets the current state of knowledge on the science and practice of salt marsh restoration, bringing together leaders across a range of disciplines in the sciences (hydrology, soils, vegetation, zoology), engineering (hydraulics, modeling), and public policy, with coastal managers who offer an abundance of practical insight and guidance on the development of programs. The work presents in-depth information from New England and Atlantic Canada, where the practice of restoring tidal flow to salt marshes has been ongoing for decades, and shows how that experience can inform restoration efforts around the world. Students and researchers involved in restoration science will find the technical syntheses, presentation of new concepts, and identification of research needs to be especially useful as they formulate research and monitoring questions, and interpret research findings. Tidal Marsh Restoration is an essential work for managers, planners, regulators, environmental and engineering consultants, and others engaged in planning, designing, and implementing projects or programs aimed at restoring tidal flow to tide-restricted or diked salt marshes.